Adhesion properties of modified bitumen - Grigorov, Andrey; Mardupenko, Aleksey; Sinkevich, Irina; Tulskaya, Alena (My University, 2020)
The article presents the results of determining the adhesion properties of bitumen modified with polymeric additives based on polypropylene and polystyrene foam with graphite additives. It has been found that a sample with the addition of 3% (mass.) Polypropylene (peel strength of the plate 2.47 N/cm²; peel of the coating from the marble plate at a speed of 7000 rpm; shift of marble plates by 5000 rpm) has the best adhesive properties. And at a polymer concentration of 10% (mass.), The best properties are manifested in a sample containing polystyrene foam with graphite additives (plate tear-off force 3.15 N/cm²; tear-off occurs at a speed of 8000 rpm; marble plates shift by 8000 rpm ).
Keywords: prospect; structure; reservoir quality; volumetric